The Peptide Visualizer and COVID-19 Protein Feature Captivation - Samuel Krem (Research Aspects in Biological Science Vol. 3, 2022)
The peptide visualizer was developed to capture the key features of coronavirus peptides through RGB color and geometric shapes depending on the amino acid type, molecular weight, charge, and polarity. In this way, the plots display the sequence and functional features of the peptides. It provides a distinctive view to peptide characteristics across different coronavirus species. As demonstrated in the article, the tool successfully distinguished the S protein RBD region in the four coronavirus subtypes: OC43, HKU1, MERS and SARS. The visualizer is sensitive to small changes in peptide sequences and has the potential to improve coronavirus diagnosis, treatment, and prevention. The program can be used for more than just plotting coronavirus peptides. It may be used to visualize changes in peptide sequences, structures, and functions in both prokaryotes and eukaryotes.